Pattern of Colour Vision Anomalies Among Patients Presenting to a Tertiary Eye Center of Nepal - Dahal, Manisha; Gautam Adhikari, Pragati; Bhattarai, Sanjeev; Mishra, Sanjeeb (Journal of Institute of Medicine Nepal, 2021)
Introduction Colour vision deficiency (CVD) is the inability to clearly differentiate colour differences under normal lighting condition. People are unaware of colour vision defect due to which they suffer in various aspects of their career. The purpose of this study was to explore the colour vision defect pattern among patients attending tertiary eye centre, Kathmandu, Nepal. Methods A hospital based, retrospective study was conducted to evaluate the defective colour vision pattern in patients attending B.P. Koirala Lions Centre for Ophthalmic Studies, Institute of Medicine, Kathmandu, Nepal where total of 692 subjects medical case sheets were reviewed and included in the study from September 2018 to April 2019. Results Among 692 patients enrolled in the study, 272(39.30%) patients were found to have CVD . Among 272 CVD, 227(83.45%) were males and 45(16.54%) were females. Congenital colour vision defect was found in 139 (26.73%) males and 21 (13.81%) females. Acquired color vision defect was found in 88 (16.92%) males and 24 (15.78%) females . When congenital CVD was observed, deutan (28.3%) CVD was more prevalent than protan (22.79%) and tritan defect (7.72%). For acquired CVD, non-specific type of CVD (8.92%) was more prevalent followed by tritan CVD (5.35%). Conclusion Significant proportion of patient presenting for eye care at tertiary eye hospital have color vision defects. Congenital CVD was found more in males than females whereas acquired color vision defect was found almost in same proportion in both males and females.